Significance of deep T-wave inversions in asymptomatic athletes with normal cardiovascular examinations: practical solutions for managing the diagnostic conundrum. (24th October 2012) - Wilson, M G; Sharma, S; Carré, F; Charron, P; Richard, P; O'Hanlon, R; Prasad, S K; Heidbuchel, H; Brugada, J; Salah, O; Sheppard, M; George, K P; et al.
Abstract : Preparticipation screening programmes for underlying cardiac pathologies are now commonplace for many international sporting organisations. However, providing medical clearance for an asymptomatic athlete without a family history of sudden cardiac death (SCD) is especially challenging when the athlete demonstrates particularly abnormal repolarisation patterns, highly suggestive of an inherited cardiomyopathy or channelopathy. Deep T-wave inversions of ≥2 contiguous anterior or lateral leads (but not aVR, and III) are of major concern for sports cardiologists who advise referring team physicians, as these ECG alterations are a recognised manifestation of hypertrophic cardiomyopathy (HCM) and arrhythmogenic right ventricular cardiomyopathy (ARVC). Subsequently, inverted T-waves may represent the first and only sign of an inherited heart muscle disease, in the absence of any other features and before structural changes in the heart can be detected. However, to date, there remains little evidence that deep T-wave inversions are always pathognomonic of either a cardiomyopathy or an ion channel disorder in an asymptomatic athlete following long-term follow-up. This paper aims to provide a systematic review of the prevalence of T-wave inversion in athletes and examine T-wave inversion and its relationship to structural heart disease, notably HCM and ARVC with a view to identify young athletes at risk of SCD during sport. Finally, the review proposes clinical management pathways (including genetic testing) for asymptomatic athletes demonstrating significant T-wave inversion with structurally normal hearts.